EFEKTIVITAS PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA BOLABULU KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Alfian Alfian (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
The Village Musrembang which was held in Bola Bulu Village, Pitu Riase District, Sidenreng Rappang Regency was the lowest level or the initial stage of the musrembang, which started from the village musrembang which was the implementation of the village development planning deliberation, so that a good development planning document was obtained, but in its implementation the results of the musrembang The village does not yet have a good planning foundation. The purpose of this study was to determine the effectiveness of the implementation of the development planning Deliberation of Bola Bulu Village, Pitu Riase District, Sidenreng Rappang Regency and the factors that influence the effectiveness of the implementation of the development planning Deliberation of Bola Bulu Village, Pitu Riase District, Sidenreng Rappang Regency. Data collection techniques used in this study were observation, questionnaires, interviews and document review. The collected data was then analyzed using frequency and percentage tables. The population and sample in this study were the people of Bola Bulu Village who participated in the village musrembang as many as 53 people. Based on the results of this study, it can be concluded that the effectiveness of the implementation of the development planning deliberation of Bola Bulu Village, Pitu Riase District, Sidenreng Rappang Regency is 65% good enough while the factors that affect the effectiveness of the implementation of the development planning Deliberation of Bola Bulu Village, Pitu Riase District, Sidenreng Rappang Regency, namely the education of village musrembang participants. not good 47.25%, the experience of the participants in the village musrembang is 64.50% and the lack of facilities and infrastructure is very inhibiting in the village musrembang 88.25%.